Investigation of the Relationship between Bureaucratic School Structure and Principal Management Styles - Alanoglu, Muslim; Demirtas, Zulfu (Dergipark Akad, 2020)
The purpose of this study was to investigate the relationship between school bureaucratic structure and principal management style according to teachers' perceptions. Relational-survey model was used to achieve this purpose. The sample of the study consisted of 286 teachers working in high schools in the city center of Mersin in 2017-2018 academic year. The research data were collected with the help of the Enabling School Structure and Perceived School Principal Management Styles scales. In the study, the bureaucratic structure of the schools was found to be usually enabling and sometimes obstructive. Principals often exhibit cooperative, sometimes authoritative, rarely indifferent and resistant management styles. Between enabling structure and cooperative management style was found high and positive; between enabling structure and authoritative, indifferent and resistant management style there was moderate and negative relationship. There was moderate and negative relationship between obstructive structure and cooperative management style; there was moderate and positive relationship between authoritative, indifferent and resistant management style. The enabling structure predicted the cooperative management style highly positive and the obstructive structure predicted low and negative. While the enabling structure did not predict the authoritative, indifferent and resistant management style, the obstructive structure positively predicted all three management styles.
Keywords: bureaucratic structure; management style; school; principal